Egoistic and altruistic behaviors in tobacco control campaign: the role of social media exposure, interpersonal communication and attitudes - Liu, Shiyu; Wu, Qiaofei; Luo, Xinyuan; Chen, Yu; Xu, Jing (Frontiers in Communication, 2023)
A growing body of research has examined the relationship between media exposure to health campaign information and health behaviors, yielding inconsistent findings. To address this inconsistency, it is crucial to investigate the underlying mediation and moderation mechanisms. Building upon the social diffusion model, this study explores the mediating role of interpersonal communication and the moderating role of attitudes in the relationships between health behavioral outcomes and exposure to campaign information. The results of an online survey involving 326 Chinese non-smokers and quitters suggest that social media exposure to campaign information is indirectly associated with both egoistic and altruistic behavioral intentions through interpersonal communication. However, attitudes towards tobacco control weaken the association between social media exposure to campaign information and interpersonal communication about tobacco risks. Furthermore, the indirect effect of social media exposure to campaign information on egoistic and altruistic behavioral intentions, mediated by interpersonal communication about tobacco risks, is contingent upon attitudes towards tobacco control. This study contributes to the existing literature on the health effects of campaign information exposure and provides implications for the design of health campaigns to more effectively promote healthy behaviors.